The reform of public education in 1984 in the USSR: a regional aspect (by the materials of Penza region) - V.V. Povalikhin (Известия высших учебных заведений. Поволжский регион: Гуманитарные науки)
Background. In modern Russian historiography, the crisis and collapse of state-hood at the turn of the 1980s and 1990s are considered as catastrophic results of the socio-cultural transformation of the USSR. In this context, the relevance of the work is due to the need for a scientific analysis of reforms in the field of education as one of the most im-portant resources for the adaptation of Soviet society to the challenges of the time, reflect-ing the specifics of the socio-cultural transition. The appeal to regional aspects is deter-mined by the low degree of study of the educational reform of 1984 based on the materials of Penza region. The purpose of this work is to analyze the reform of the education system in 1984 in Penza region. Materials and methods. The research was carried out on the basis of historical sources identified in the funds of the State Archive of the Russian Federation, State Archive of Penza region, as well as ideological materials and normative legal acts. In solving research problems, methods of systematic analysis of historical processes, as well as comparative study of historical sources of various species were used. Results. The study examined the general principles, goals and objectives of the 1984 reform, the results of the implementation of this reform in various areas in the Penza region in the period from 1984 to 1987. The main achievements and problems in the implementation of measures at the level of cities, districts and entire region were identified. The dynamics of the activities of local authorities in various areas of reforming the public education system is considered. Conclusions. The need to reform the education system in the USSR was due to the slow-down in the socio-economic development of the country, the decline in the quality of knowledge and professional skills among graduates of the public education system. The fol-lowing were highlighted as priority tasks for the implementation of reforms: improving the structure and content of school education, developing labor training and education, increas-ing the status and role of a teacher in society. With some success in the implementation of the reform, it is worth recognizing that none of the tasks set has been solved definitively. And the democratization processes that began in the USSR gave rise to a radical restructur-ing of the structure and content of education and educational policy in general.